ANALISIS POSTUR BURUH PADA AKTIVITAS MANUAL MATERIAL HANDLING DI PT. SEMEN TONASA DENGAN MENGGUNAKAN METODE OVAKO WORKING ANALIYSIS SYSTEM (OWAS) - Fajar, Ardiansyah; Pawennari, Andi; Safutra, Nur Ihwan; Fole, Asrul; Safitri, Khoerun Nisa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
This study was conducted at PT. Semen Tonasa, located in Biringere Village, Bungoro District, Pangkep Regency. The company operates in cement production and involves manual material handling (MMH) activities in the packing section, particularly during the loading of cement into trucks. These activities potentially lead to improper working postures that do not align with workers’ physical capabilities, resulting in the risk of musculoskeletal disorders (MSDs). The objectives of this study are to identify worker fatigue and discomfort during MMH activities, analyze working postures, and provide improvement recommendations using the Ovako Working Posture Analysis System (OWAS) and the Nordic Body Map (NBM) methods. The analysis revealed that handling loads of 40 kg results in various working postures with differing levels of risk. Out of the 10 observed postures, 2 were categorized as Level 1 (no risk), 6 as Level 3 (high risk, requiring immediate improvement), and 2 as Level 4 (very high risk, requiring urgent correction). Additionally, workers reported discomfort in 13 body parts and pain in 6 body parts. These findings emphasize the importance of improving working postures to prevent and reduce the risk of MSDs among workers.